2001
DOI: 10.1152/ajpregu.2001.281.4.r1071
|View full text |Cite
|
Sign up to set email alerts
|

Impaired renal D1-like and D2-like dopamine receptor interaction in the spontaneously hypertensive rat

Abstract: D(1)-like (D(1), D(5)) and D(2)-like (D(2), D(3), D(4)) dopamine receptors interact in the kidney to produce a natriuresis and a diuresis. Disruption of D(1) or D(3) receptors in mice results in hypertension that is caused, in part, by a decreased ability to excrete an acute saline load. We studied D(1)-like and D(2)-like receptor interaction in anesthetized spontaneously hypertensive rats (SHR) by the intrarenal infusion of Z-1046 (a novel dopamine receptor agonist with rank order potency of D(3)> or =D(4)>D(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
112
1
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 66 publications
(120 citation statements)
references
References 40 publications
5
112
1
2
Order By: Relevance
“…Moreover, these animals have a defect in dopamine D1 receptor function similar to the one observed in human essential hypertension and spontaneously hypertensive rats (11,12). Although a large body of data has accumulated to indicate increased oxidative stress in hypertension and type 2 diabetes (14 -20), it is unclear whether this phenomenon is responsible for decreased insulin sensitivity, impaired D1 receptor function, and increased blood pressure observed in obese Zucker rats.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, these animals have a defect in dopamine D1 receptor function similar to the one observed in human essential hypertension and spontaneously hypertensive rats (11,12). Although a large body of data has accumulated to indicate increased oxidative stress in hypertension and type 2 diabetes (14 -20), it is unclear whether this phenomenon is responsible for decreased insulin sensitivity, impaired D1 receptor function, and increased blood pressure observed in obese Zucker rats.…”
Section: Discussionmentioning
confidence: 92%
“…Although the precise nature of renal D1 receptor dysfunction in human and animal models of hypertension and in obese Zucker rats remains to be elucidated, there is increasing evidence that the reduced renal effects of dopamine are due to defects in the D1 receptor itself, in both ligand binding and the receptor-G-protein coupling (7,(11)(12)(13). We have shown that renal D1 receptors in obese Zucker rats are unable to bind ligands and couple to G-protein despite normal G-protein expression (7).…”
mentioning
confidence: 99%
“…Se demostró que el polimorfismo se encuentra en el sitio de unión del microARN miR-504, localizado en la región 3´UTR del gen. El polimorfismo rs686 reside en la parte del 3´UTR complementaria a la secuencia de unión del miR-504; la adecuada complementariedad es crítica en la función de unión del microARN ; el cambio de A a G, reduce la unión del microARN y, por lo tanto, la eficiencia en el expresión del receptor de dopamina(84) este microARN actúa sobrerregulando la expresión del gen, de tal manera que habrá una mayor expresión de los receptores DRD1 en los individuos portadores del alelo A. Los efectos de la dopamina mediados por los receptores D1 (DRD1) se han asociado con la regulación de la presión arterial por medio de la estimulación de la diuresis y natriuresis, y del aumento de la vasodilatación (85,86). La activación de DRD1 por la dopamina responde por el 50 % de la excreción de sodio en condiciones basales (87); por ello, la deficiencia intrarrenal de dopamina puede llevar a hipertensión (88).…”
Section: Discussionunclassified
“…This mechanism is similar to but distinct from homologous desensitization (18,19) because the uncoupling in hypertension is independent of renal dopamine levels (3,16,20). Similarly, the uncoupling is not due to heterologous desensitization because the responsiveness of other G protein-coupled receptors (e.g., parathyroid hormone, ␤-adrenergic, and cholecystokinin receptors) remains intact in the prehypertensive spontaneously hypertensive rat (3,8,(21)(22)(23).…”
mentioning
confidence: 88%